Igreja de Santana do Bujaru caracterização tipológica, histórica e estilística a partir de suas referências documentais, físicas e icônicas - NASCIMENTO, Claudia Helena Campos (Universidade Federal do Pará, 2017)
This study aimed to characterize and understand the architectural object at physical, historical and visual aspects, by documents, reports and especially from the architectural object itself. Based on the material object - architectural - and the cultural object - social heritage and history - were used methodological approaches physics research (surveys, photographic records, material and technical analysis), history (documentary and iconographic) and ethnography as a means to understand relations of the church of Santana do Bujaru (Bujaru/PA) with the site and region, and the importance of the building to the community, identifying the relationship of belonging and ownership over time, that characterize its importance as a cultural heritage.